The Influence of Work Discipline and Motivation on Employee Performance at the Takalar Regency Regional Financial and Asset Agency Office - Faidah, Nur; Muchriady Muchran, Akhmad Akhmad, (YUME : Journal of Management, 2025)
This study aims to analyze the influence of work discipline and motivation on employee performance at the Regional Financial and Asset Agency of Takalar Regency. The research employs a quantitative approach with a descriptive explanatory method. The population in this study consists of all employees at the agency, totaling 51 individuals, which also serves as the research sample using a saturated sampling technique. Data collection was conducted through questionnaires and direct observation to obtain both primary and secondary data sources. The analytical tools used include validity and reliability tests, classical assumption tests (normality, multicollinearity, and heteroscedasticity), multiple linear regression analysis, and hypothesis testing with the assistance of SPSS version 26 software. The findings indicate that work discipline has a positive but not statistically significant effect on employee performance. This is evidenced by a t-count value of 1.920 which is greater than the t-table value of 1.677, but with a significance level of 0.061, which exceeds the standard threshold of 0.05. On the other hand, work motivation shows a positive and significant influence on employee performance. This is supported by a t-count value of 2.799 greater than 1.677, and a significance value of 0.007, which is below 0.05. These results suggest that while both work discipline and motivation are positively correlated with performance, only motivation has a significant impact in this context. The study concludes that increasing employee motivation should be a strategic focus for improving performance outcomes within the agency. Meanwhile, efforts to enhance work discipline may require a more long-term or structural approach, given its currently insignificant statistical effect. The implications of this research highlight the importance of understanding internal behavioral factors in public sector performance management.